ANALISIS KINERJA DEWAN PERWAKILAN RAKYAT DAERAH KOTA PALU DALAM PEMBUATAN PERATURAN DAERAH (Studi Kasus Peraturan Daerah Tentang Pajak Daerah) - Ishak, Ishak (Katalogis, 2013)
This research aimed: first, to analyze the Indonesian Legistative Assembly performance at Municipal level Palu City’s in making provincial regulation (case study of provincial regarding local taxes). Second, to know the factors influenced the Indonesian Legistative Assembly performance at Municipal level Palu City’s in making provincial regulation (case study of provincial regarding local taxes). The research method used was descriptive qualitative, population of this research was all members os Special Committtee of the Indonesian Legistative Assembly performance at Municipal level Palu City’s, executives of NGO were 37 persons with the sample were 13 respondents determined by using sampling, the collected data was analyzed qualitatively by describing in systematically and analytically concerning the individual characteristics, facts, condition, or group. The research result sjowed the obtained scores of thr four indicators of this research were catagorized good. While the supporting factors for the the Indonesian Legistative Assembly performance at Municipal level Palu City’s were first, the willingness of members of special committee in communication involvement with related parties towards their duties, second, the members of special committee attitude and behavior, and third, the members of special committee seriousness in doing their duties. While the restricting factors were first, the members of special committee dicipline in doing their duties, second, lack of the members of special committee ability in understanding leader’s instructions, third, limited capability of the members of special committee in using the available aquipments.